When the last child moves out: Continuity and convergence in spouses' housework time. Issue 1 (18th July 2022) - Schulz, Florian; Raab, Marcel
Abstract: Objective: To examine how mothers' and fathers' time allocation for routine housework changes when the last child moves out of the family household. Background: During the transition to the empty nest, parental households are reduced to the situation before parenthood. Mothers and fathers are released from their direct parenting roles and parental time binds. This gradual transition creates a context in which housework time allocation is likely to be rearranged. Methods: Changes in mothers' and fathers' absolute and relative routine housework hours were estimated with longitudinal fixed effects regression models, using data from the German Socio‐Economic Panel Study (1991–2020) on 890 households experiencing the transition to the empty nest. Results: Mothers' reduced their time for routine housework by 9 minutes on regular weekdays at the transition to the empty nest, whereas fathers' routine housework hours were largely unaffected when the last child moved out of the parental household. Mothers' routine housework share was slightly below 80% in the years around this event. Separate analyses for mothers with different education revealed only minor variations in the gendered trajectories of housework time. In sum, mothers continued to do the majority of housework in this phase of the life course despite some slight convergence. Conclusion: The transition to the empty nest contributes slightly to the life‐course convergence of housework time and, thus, similar to all major life‐course transitions following the birth of children, tends to reduce housework inequality in couples.